2023
DOI: 10.1021/acs.langmuir.3c00733
|View full text |Cite
|
Sign up to set email alerts
|

Chain End-Functionalized Dense Polymer Brushes from an Inimer Coating by SI-RAFT

Julia D. Smith,
Luis Adrian Padilla Salas,
Carter Kreft
et al.

Abstract: Polymer brushes with controllable grafting density are grown on an inimer coating bearing Reversible Addition-Fragmentation Chain Transfer polymerization (RAFT) chain transfer agents (CTAs). The inimer coating is cross-linked on the substrate to provide an initiator layer that is stable during exposure to organic solvents at high temperatures. Surface-initiated RAFT is conducted to grow poly­(2-vinylpyridine) (P2VP) brushes on the coating at grafting densities approaching the theoretical limits. This methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Smith et al reported the synthesis of polymer brushes via RAFT of poly(2-vinylpyridine) (P2VP) on an inimer-coated silica surface, which exhibits high chemical stability against many organic solvents even at high temperatures. 108 The synthetic pathway chosen yields high grafting densities and allows the end-group functionalization for the generation of low surface energy domains after thermal annealing by thiol–ene ‘click’ chemistry. An alternative field of application for polymer brushes synthesized by “grafting-from” RAFT is shown by Choi et al 109 Polymer brushes of di(ethylene glycol) methylether methacrylate (DEGMA) were synthesized on titanium-coated glass substrates, which illustrated excellent anti-fouling properties and can be further tuned to allow cell adhesion after coupling of arginyl glycyl aspartic acid (RGD).…”
Section: Enzyme-initiated Raft Polymerizationmentioning
confidence: 99%
“…Smith et al reported the synthesis of polymer brushes via RAFT of poly(2-vinylpyridine) (P2VP) on an inimer-coated silica surface, which exhibits high chemical stability against many organic solvents even at high temperatures. 108 The synthetic pathway chosen yields high grafting densities and allows the end-group functionalization for the generation of low surface energy domains after thermal annealing by thiol–ene ‘click’ chemistry. An alternative field of application for polymer brushes synthesized by “grafting-from” RAFT is shown by Choi et al 109 Polymer brushes of di(ethylene glycol) methylether methacrylate (DEGMA) were synthesized on titanium-coated glass substrates, which illustrated excellent anti-fouling properties and can be further tuned to allow cell adhesion after coupling of arginyl glycyl aspartic acid (RGD).…”
Section: Enzyme-initiated Raft Polymerizationmentioning
confidence: 99%
“…Most commonly, self-assembled monolayers (SAMs) have been used to grow homopolymer and mixed brushes by grafting-from methods . To overcome some of the limitations of SAMs, such as limited stability to various reagents, substrate-dependent anchoring chemistry, degrafting of swollen brushes, and nonhomogeneous distribution of initiators, , and to achieve high grafting density A/B mixed brushes, we have developed ultrathin, cross-linkable inimer-containing coatings for brush growth using controlled radical polymerization methods. , These coatings contain either two types of inimers that can orthogonally grow A and B brushes, respectively, or a Y-shaped inimer that bears two distinct initiators attached at a single junction point for high grafting density mixed A/B brush growth by sequential surface-initiated atom transfer radical polymerization (SI-ATRP) and nitroxide-mediated polymerization (SI-NMP). , The Y-inimer coating is especially useful for the synthesis of mixed PE brushes as it ensures intimate contact between oppositely charged brushes and an equal grafting ratio.…”
Section: Introductionmentioning
confidence: 99%